A kinetic model of the gelation of konjac glucomannan induced by deacetylation. (1st June 2017) - Mao, Ching-Feng; Chen, Cheng-Ho
Highlights: The gelation of konjac glucomannan exhibits an induction period. A kinetic model was proposed for the induction period. Modulus evolution during gelation was described by the kinetic model with the help of a cascade formalism. The kinetic parameters were extracted from experimental data. Abstract: The gelation of konjac glucomannan (KGM) often involves an induction period featured by an initial drop in modulus. The gelation kinetics recorded as a time-dependent modulus change is composed of an initial drop followed by a steady increase in modulus until an equilibrium stage is reached. In this work, the time-dependent modulus curve is described by a kinetic model which incorporates the cascade theory with the kinetic equations consisting of sequential reactions of deacetylation and cross-link formation. The proposed model is capable of predicting the presence of the induction period and the kinetic parameters can be extracted from the concentration dependence of the initial drop. A rheological experiment of KGM gelation using sodium carbonate as deacetylation agent was conducted to illustrate the feasibility of the proposed fitting approach, which yields kinetic curves agreeing satisfactorily with the experimental results.